Isolation of new white collar mutants of Neurospora crassa and studies on their behavior in the blue light-induced formation of protoperithecia. - Degli-Innocenti, F (1984)
White collar (wc) mutants of Neurospora crassa are thought to be regulatory mutants blocked in the photoinduction of carotenogenesis. Eight new wc mutants have been isolated after UV mutagenesis; their morphology and linear growth rate are not altered, although blue light-induced carotenogenesis is completely blocked. All of the wc mutations fall into two complementation groups corresponding to the already-known wc-1 and wc-2 loci. It is shown that the wc mutations impair another blue light effect, the photoinduction of protoperithecia formation, as well as the low constitutive production of protoperithecia in the dark. These effects are not due to the lack of carotenoids since the albino mutants show a normal sexual development. The pleiotropic effects of the mutations in the wc genes indicate that they play a key role in the mechanisms of regulation of the blue light-induced responses of N. crassa.